Codistribution of pericellular matrix proteins in cultured fibroblasts and loss in transformation: Fibronectin and procollagen - Vaheri, Antti (1978)
Antibodies to fibronectin and to distinct types of procollagens and collagens were used in immunofluorescent staining to localize these proteins in cell cultures. Normal human skin or lung fibroblasts produced a fibrillar pericellular matrix in which fibronectin and procollagen (types I and III) showed extensive codistribution. Fibronectin and procollagen were synthesized by the same cells as judged by double-stain immunofluorescence. Pericellular procollagen was specifically digested with collagenase without an effect on the fibrillar distribution of matrix fibronectin. Brief treatment with trypsin removed both matrix proteins. The human tumor cell lines HT-1080 (fibrosarcoma) and RD (rhabdomyosarcoma) produced little or no matrix fibronectin or procollagen. At sites of cell contact, simian virus 40-transformed lung fibroblasts (VA13) produced small amounts of pericellular fibrillar matrix fibronectin that codistributed with procollagen type I. Intracellular fibronectin and procollagen were visualized in all of these human sarcoma cell lines. When chicken embryo fibroblasts infected with a T class mutant (NY68) of Rous sarcoma virus temperature-sensitive for transformation were maintained at the nonpermissive temperature (41°) the cells had normal phenotype and a fibrillar matrix containing fibronectin and procollagen was present. At the permissive temperature (35°), the cells showed transformed phenotype and the matrix was lost. The failure to produce a pericellular fibronectin/collagen matrix may account for several phenotypic characteristics of transformed cultured fibroblasts.